(untitled) (Contemporary Mathematics, 2023)
In this article, we aim to provide a solution for the Markovian Erlang non-constricted queue that takes into account encouraged arrival, balking feedback strategy, and customer retention, all in a steady state. Our approach involved using an iterative technique to determine the probability of “n” customers in the system occupying stage “s”, the probability of an empty system, and the efficiency of the queuing system. To illustrate the relationship between probability and these additional concepts, we present numerical data.